The Effect Of Intellectual Capital On Competitive Advantage And Company Performance As A Moderating Variable - Ahmad Badawi; Lucky Nugroho; Nurul Hidayah; Anees Jane Ali (Universitas Udayana, 2024)
The global Covid-19 pandemic is a big challenge for mining companies in 2020. So far, the demandfor tin mining products has fallen quite sharply amid world fluctuations that continue to fluctuate.As developing countries struggle to survive and prosper, new standards are being set andcompanies around the world are increasingly competing for higher records. Mining companiesmust continuously increase their competitive advantage and efficiency through the best use of theirresources, both tangible and intangible. The purpose of this research is to analyze the effect of creditinstitutions on competitive advantage variables and to regulate financial performance.Quantitative research methods using multiple regression. Usage data is secondary data in the formof financial reports and publication reports for 2020-2021. The result of the research is IC has noeffect on the Company's Competitive Advantage. ROA significant negative effect, which meansthat increasing the company's ROA does not increase the company's advantage, and ROA doesnot strengthen the moderating influence of IC on Competitive Advantage.